Jungian personality type preferences of female and male Hungarian leaders - Szathmári, Edit; Czibor, Andrea; Bents, Richard; Szabó, Zsolt Péter; Kiss, Orhidea Edith (Frontiers in Psychology, 2023)
In this study, we investigated the personality type preferences of female and male Hungarian nonmanagerial individual contributors, middle managers, and executives. We aimed to investigate the preferences among successful females and males (i.e., executives) compared to non-executives. The preference distinctions between successful females and males were also analyzed. We conducted a cross-sectional analysis using the Jungian-based Golden Profiler of Personality (GPOP) questionnaire (N = 5376; 2678 females, 2698 males; average age 35.98 with an SD = 8.977). Executives scored higher in extraversion, intuition, thinking, perceiving, and calm preferences compared to middle managers and individual contributors while scoring lower in sensing and tense preferences. Extraversion, intuition, and feeling preferences were more prevalent among female executives than both male executives and women in general. Our findings suggest that Hungarian female executives' personality preferences align with either stereotypically feminine traits (intuitive and feeling) or male executive-like preferences (extraverted, sensing, thinking, and judging combination). We also discussed the influence of cultural norms and expectations on the personality preferences of female and male executives. Our results are in line with prior research conducted in the Western context, however, the gender differences are more striking. We concluded that men have a reasonable chance of success across a spectrum of personality preferences as they ascend the hierarchy, while women need to exhibit specific preferences to be successful on the same journey. The self-descriptive and cross-sectional nature of our data spell limitations, therefore we suggest conducting future longitudinal studies, including explanatory and contingency variables (e.g. perceived cultural norms).